It's better this way : a novel - Macomber, Debbie (Ballantine Books, 2021)
"After divorce shatters her family, one woman's struggle to pick up the pieces finally leads to a new beginning--but is the past truly behind her? #1 New York Times bestselling author Debbie Macomber explores the powerful intersections of love and family in this poignant novel"--